The Influence of Plant Age and Microbes-Enzymatic Additives on Fermentation of Total Mixed Ration Silages of Capiaçu Grass (Pennisetum purpureum, Schum) - J. P. Alves; E. S. J. Galeano; M. A. P. Orrico Junior; T. Fernandes; M. Retore; M. S. J. da Silva; A. C. A. Orrico; L. da S. Lopes (Tropical Animal Science Journal, 2022)
The conservation of elephant grass cultivar Capiaçu in the form of total mixed ration (TMR) silage can help to improve the quality of the fermentative process and optimize feed management. However, the best cutting age of grass and the necessity of using microbes-enzymatic additives to aid in the process have not been determined thus far. Therefore, the objective of this study was to evaluate cutting age and different microbes-enzymatic additives on the fermentative and nutritional quality of total mixed ration (TMR) silages based on BRS Capiaçu. A completely randomized design was used in a 3×3 factorial scheme, with three cutting ages of grass (60, 90, and 120 days of regrowth), associated with three types of additives [CON (control), HOM (homofermentative inoculant + fibrolytic enzyme), and COMBO (homofermentative inoculant + heterofermentative inoculant + fibrolytic enzyme)]. The fermentative losses, the production of organic acids, chemical composition, and the aerobic stability of the tested silages were measured. The TMR silages containing 60-day-old grass showed the lowest dry matter contents, highest effluent production, and lower aerobic stability. The COMBO inoculant application provided higher acetic acid contents and greater aerobic stability of the 90- and 120-day-old grass silages. The highest lactic acid concentrations were observed in silages produced with the 60- and 90-day-old grass silages. It is concluded that the TMR produced with BRS Capiaçu at 90 days of age and in association with COMBO is the best option to balance the nutritional and fermentative quality of this type of silage.